Effects of a Tele-Prehabilitation Program with Indirect Electrostimulation Compared to Home-Based Exercise in Patients Eligible for Lower Limb Arthroplasty: A Randomized Controlled Trial - Patanè, Pamela; Carnevale Pellino, Vittoria; Febbi, Massimiliano; Cavallo, Caterina; Gervasoni, Fabrizio; Gatti, Alessandro; Caldarella, Emanuele; de Caro, Francesca; Vandoni, Matteo; Manzoni, Federica; Marin, Luca (Journal of clinical medicine, 2025)
Background/Objectives: Hip and knee arthroplasty relieves pain, restores mobility, and improves function in severe joint damage, though pain and strength loss may persist post-surgery. Better pre-surgery function and activity predict improved arthroplasty outcomes. Prehabilitation programs enhance functional abilities, reducing hospitalization duration, and lowering peri-surgery complication risks. This study aims to evaluate the efficacy of four weeks of different modalities of tele-home-prehabilitation programs on perceived pain and functional capacity in patients who are eligible for hip or knee arthroplasty. Methods: Forty-four patients (aged 65-80 years) eligible for elective lower limb arthroplasty were enrolled in the present randomized controlled trial study. Participants were randomly assigned to the Electrostimulation Group (EG) or the Home-Based Exercise Group (HG). The EG performed underwent teleprehabilitation program using indirect neuromuscular electrostimulation therapy, while the HG performed home-based exercise supervised by a sports specialist. Functional capacity was assessed with the Timed Up and Go test (TUG), the 30 s Chair Stand test (30CST) and the Six-Minute Walking Test (6MWT). Quality of life was assessed with the Oxford Hip Score (OHS) or Oxford Knee Score (OKS), depending on the participants' surgery. The Technology Acceptance Model (TAM) questionnaire was completed by the EG after the intervention. Results: No significant differences were found among groups in the 30CST and TUG tests. The analyses revealed significant differences for the Oxford Questionnaires and 6MWT. Conclusions: Our study highlights the potential of teleprehabilitation using indirect neuromuscular electrostimulation to improve walking autonomy and quality of life of individuals who are candidates for lower limb arthroplasty.
Keywords: arthroplasty; teleprehabilitation; indirect neuromuscular electrostimulation